Validity and Reliability Analysis of a Contextual Problem-Based Essay Test For Mathematical Critical Thinking on Cubes and Rectangular Prisms - Imelda; Izwita Dewi; KMS Muhammad Amin Fauzi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study aimed to develop and evaluate a contextual problem-based essay test for assessing students' mathematical critical thinking skills on the topics of cubes and rectangular prisms. A quantitative descriptive design was employed involving 30 ninth-grade students from SMPN 31 Medan during the pilot-testing stage. Prior to implementation, the instrument was evaluated by expert validators to establish content validity. Empirical item validity was analyzed using the Pearson Product–Moment correlation coefficient, while internal consistency reliability was estimated using Cronbach's Alpha. The findings showed that all essay items met the criterion of empirical validity and that the instrument demonstrated moderate internal consistency, indicating its suitability for preliminary classroom assessment and pilot testing. The developed instrument assesses higher-order cognitive processes based on Facione's critical thinking framework, including interpretation, analysis, evaluation, inference, and explanation, through authentic contextual geometry problems. This study contributes to mathematics education by providing a contextually relevant assessment instrument with preliminary psychometric evidence that can support teachers in implementing authentic assessment of mathematical critical thinking skills. The findings also provide a foundation for future large-scale validation studies aimed at developing standardized assessment instruments for mathematics education.